FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Vinsensia Vania Heng; Vidyarto Nugroho (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence whether firm size, profitability, leverage, firm growth, liquidity, and activity affect firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample selection method used in this research is purposive sampling. The sample used in this study were 35 companies. The data processing technique used is multiple regression analysis assisted by the EViews 10 program and Microsoft Excel 2007. The results show that profitability has a positive effect on firm value, and firm growth has a negative effect on firm value, while firm size, leverage, liquidity, and activity does not affect firm value. The implication of this research is the need to increase profitability which will increase the firm value which will be a positive signal for investors.